Potential of palm kernel activated carbon epoxy (PKAC-E) composite as solid lubricant: effect of load on friction and wear properties - Abdollah, Mohd Fadzli; Amiruddin, Hilmi; Chua, Khai Wei; Mat Tahir, Noor Ayuma (Malaysian Tribology Society, 2014)
The aim of this study is to investigate the effect of load on the friction and wear properties of palm kernel activated carbon epoxy (PKAC-E) composite. The PKAC-E composite specimen was fabricated by hot compression molding method. Dry sliding test was performed by using a pin-on-disc tribometer at various load conditions with constant sliding speed and distance. The experimental results show that wear rate and friction coefficient of PKAC-E composite decreases with applied load. However, at higher load, friction coefficient increases slightly and remains almost invariant with applied load. In addition, some adhesive and abrasive wear types were identified on the worn surfaces. The main conclusion of this work is that PKAC-E composite show unique properties as solid lubricant at low load under unlubricated conditions.